Partial left ventriculectomy: a retrospective study - Christo,Marcelo Campos (2003)
OBJECTIVE: To identify useful predictive data on chance mechanisms of postoperative outcome, the impact on symptoms of terminal heart failure - after partial left ventriculectomies (PLV) - was critically evaluated through the analysis of results, on accumulated descriptive data on reports, between 1995 and 1998. METHOD: Available routine clinical data on surgical aspects and clinical outcomes were gathered and, when possible, validated for comparative analysis. RESULTS: PLV can provide a significant short to medium term amelioration in the quality-of-life in event-free survivors, but it was also watched out that in important proportion of them - as an evolutive sequence - PLV was incapable of changing the myocardial fibers leading tendency to conservatism of the preoperative vicious geometric dynamic pattern in late evolution. Importantly, the LV end-diastolic echocardiographic diameter of 7.5 cm (± 1.4 cm) was the steadiest quantitative significant numerical appeal to heart reduction surgery, in a setting of 465 patients, aged two to 74 years. And in a succession of individual reports of PLV results, whose mortality varied from 0 a 60%, survival after PLV showed a significant relationship with morphologic evolution of cardiomyocytes, in postoperative, and augmented in absolute values in patients with progressive ventricular dysfunction, treated with the insertion of LVAD (Left Ventricular Assist Devices). CONCLUSION: The material impossibility of identifying useful qualified predictors on chance mechanisms of postoperative outcome emerged as the crucial limitation for current usage of surgical reversal of left ventricular structural chamber dilation - to treat dilated cardiomyopathies - despite accumulated numerical values and clinical experiences.